2016
DOI: 10.1038/srep31633
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and anti-inflammatory polyhydroxylated spirostanol saponins from Tupistra chinensis

Abstract: Tupistra chinensis is widely distributed in southwestern China and its rhizome is a famous folk medicine for the treatment of carbuncles and pharyngitis. Its chemical identity of potent antiproliferative and anti-inflammatory constituents has been carried out in this study. Twenty-three polyhydroxylated spirostanol saponins, including nine novels, were isolated and identified. The new spirostanol saponins were elucidated as spirost-25(27)-en-1β,2β,3β,4β,5β-pentol-2-O-β-D-xylopyranoside (1), spirost-25(27)- en-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…There are two main types of saponin, triterpenoid saponins and steroidal saponins. Saponins have been reported to exert different pharmacological actions such as anti-inflammatory[71], immunoregulatory [72] and also antineoplastic [73]. They are also known to display antioxidant properties[74].…”
Section: Discussionmentioning
confidence: 99%
“…There are two main types of saponin, triterpenoid saponins and steroidal saponins. Saponins have been reported to exert different pharmacological actions such as anti-inflammatory[71], immunoregulatory [72] and also antineoplastic [73]. They are also known to display antioxidant properties[74].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, successful preparation examples for (25 R / S )-spiromeric epimers were accomplished by SFC isolation [ 11 , 12 ] usually. Meanwhile, it is very rare still for preparing this type of R / S mixture using HPLC methods [ 13 , 14 , 15 , 16 ]. On the other hand, among the rare isolation examples, all of them are only for the isolation of C 12 unsubstituted 25 R / S -spirostanol saponin diastereomers, but no reference was found to separate C 12 carbonylated 25 R / S -ones.…”
Section: Discussionmentioning
confidence: 99%
“…Saponins exert various pharmacological effects, including cardiovascular protective activity [4], anti-inflammatory [5], antiviral [6], and immunoregulatory effects [7]. Moreover, recent studies have reported that saponins demonstrate significant anticancer activity, such as anti-proliferation [8], anti-metastasis [9], anti-angiogenesis [10] and reversal of multi-drug resistance (MDR) effects [11] through mechanisms that include induction of apoptosis and promotion of cell-differentiation.…”
Section: Introductionmentioning
confidence: 99%